2007
DOI: 10.1021/es0628194
|View full text |Cite
|
Sign up to set email alerts
|

Parental Exposure to Pesticides and Poor Clutch Viability in American Alligators

Abstract: In central Florida, alligators (Alligator mississippiensis) inhabiting lakes contaminated with organochlorine pesticides (OCPs) produce eggs that have high OCP concentrations and low clutch viability (proportion of eggs in a clutch that yield a live hatchling) compared to those from less contaminated lakes (reference lakes). However, a clear dose-response relationship has not been established between OCPs and poor clutch viability. In order to better elucidate a cause and effect relationship between OCP exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 13 publications
1
31
0
1
Order By: Relevance
“…Adults that had been exposed to synthetic compounds over a lifetime of feeding in contaminated areas experienced endocrinological abnormalities (Guillette et al 1994) and reduced clutch success (Rauschenberger et al 2007). Offspring that succeeded in hatching frequently experienced retarded development and growth and reduced reproductive potential (Guillette et al 1994, Gunderson et al 2004, Milnes et al 2005.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%
“…Adults that had been exposed to synthetic compounds over a lifetime of feeding in contaminated areas experienced endocrinological abnormalities (Guillette et al 1994) and reduced clutch success (Rauschenberger et al 2007). Offspring that succeeded in hatching frequently experienced retarded development and growth and reduced reproductive potential (Guillette et al 1994, Gunderson et al 2004, Milnes et al 2005.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%
“…They may be additionally exposed to the demethylated metabolites through ingestion of MXC-exposed prey organisms that have biotransformed MXC. Recent studies have reported parent MXC concentrations of 0.7 ng/g in seafood from Southern China (Guo et al, 2007), between <0.35 ng/g (limit of detection) and 2 ng/g in freshwater fish captured in the Colorado river (Hinck et al, 2007), between 8 and 17 ng/g in alligator eggs from central Florida lakes (Rauschenberger et al, 2007) and 534 ng/g in fat from crocodile scute in Costa Rica (Rainwater et al, 2007). MXC was found in 5 of 36 soil samples taken from agricultural areas in British Columbia, and the average MXC concentration in these samples was 0.23 mg/ kg (Wan et al, 2005).…”
Section: Comparisons Of Conjugation and Demethylation Pathwaysmentioning
confidence: 99%
“…Alligators living in Lake Apopka, Florida, undergo a combinatorial exposure to high levels of pesticides and agricultural contamination compared with those alligators living in a nearby, but relatively pristine lake, Lake Woodruff (Heinz et al 1991, Guillette et al 1999, Rauschenberger et al 2007. A number of reproductive abnormalities, including altered gonadal development and decreased robustness of sexually dimorphic gene expression, have been reported in alligators originating from Lake Apopka (Milnes et al 2005(Milnes et al , 2008).…”
Section: Introductionmentioning
confidence: 99%